2020
DOI: 10.1186/s13071-020-3944-3
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies evaluating the efficacy of a novel orally administered combination product containing sarolaner, moxidectin and pyrantel (Simparica Trio™) for the treatment and control of flea infestations on dogs

Abstract: Background: Five studies were conducted to evaluate a novel oral combination tablet containing sarolaner, moxidectin and pyrantel (Simparica Trio ™), for efficacy against induced flea infestations, speed of kill and effects on flea reproduction on dogs. Methods: Based on pre-treatment flea counts, dogs were randomly allocated to treatment with a single, oral dose of either placebo or Simparica Trio ™ at the minimum label dose of 1.2 mg/kg sarolaner, 24 µg/kg moxidectin and 5 mg/ kg pyrantel (as pamoate salt) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…The efficacy against fleas shown in this study is consistent with that demonstrated previously for sarolaner alone in a field study [18]. Additionally, reductions in the numbers of fleas seen in the post-treatment evaluations in these dogs in this study are consistent with the rapid onset of activity of Simparica Trio ™ as demonstrated in a laboratory flea speed of kill study [19], with 100% reduction of flea egg-laying also being demonstrated in a laboratory flea reproduction study [19]. The combination of these effects results in the suppression of the flea populations in the dogs' environments by killing newly emerged fleas on the dogs before they lay eggs and contribute to the environmental re-infestation [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The efficacy against fleas shown in this study is consistent with that demonstrated previously for sarolaner alone in a field study [18]. Additionally, reductions in the numbers of fleas seen in the post-treatment evaluations in these dogs in this study are consistent with the rapid onset of activity of Simparica Trio ™ as demonstrated in a laboratory flea speed of kill study [19], with 100% reduction of flea egg-laying also being demonstrated in a laboratory flea reproduction study [19]. The combination of these effects results in the suppression of the flea populations in the dogs' environments by killing newly emerged fleas on the dogs before they lay eggs and contribute to the environmental re-infestation [20].…”
Section: Discussionsupporting
confidence: 89%
“…The combination of these effects results in the suppression of the flea populations in the dogs' environments by killing newly emerged fleas on the dogs before they lay eggs and contribute to the environmental re-infestation [20]. This flea control is consistent with a high adulticidal activity and breaking of the flea life-cycle through the cessation of flea reproduction that was seen in laboratory studies [19].…”
Section: Discussionmentioning
confidence: 66%
“…This high level of flea control is consistent with the adulticidal activity and breaking of the flea life-cycle through the cessation of flea reproduction that was seen in Simparica Trio ™ laboratory efficacy studies [17]. Against induced infections with adult C. felis and C. canis, a single oral dose of Simparica Trio ™ reduced live flea counts by ≥ 99.9% within 24 hours of treatment and by 100% within 24 hours of weekly re-infestation for 35 days [17]. Blood-feeding for at least 24 hours is required for a female flea to commence egg laying, thus fleas killed within 24 hours are not able to contribute to environmental contamination by flea eggs [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…These results are comparable to the efficacy reported previously for other orally administered pulicidal medications belonging to both the isoxazoline [13][14][15] and spinosyn class [16] in dogs. This high level of flea control is consistent with the adulticidal activity and breaking of the flea life-cycle through the cessation of flea reproduction that was seen in Simparica Trio ™ laboratory efficacy studies [17]. Against induced infections with adult C. felis and C. canis, a single oral dose of Simparica Trio ™ reduced live flea counts by ≥ 99.9% within 24 hours of treatment and by 100% within 24 hours of weekly re-infestation for 35 days [17].…”
Section: Discussionsupporting
confidence: 76%
“…Sarolaner belongs to a potent new class of ectoparasiticides (isoxazolines) and has been shown to provide consistent efficacy against fleas and ticks in Simparica ® and Simparica Trio ™ for 1 month following a minimum single oral dose of sarolaner at 2.0 and 1.2 mg/kg respectively [18][19][20]. Sarolaner exerts activity against invertebrates by blocking GABA-gated chloride channels [21,22].…”
Section: Introductionmentioning
confidence: 99%